Plasticized poly(3‐hydroxybutyrate) with improved melt processing and balanced properties. Issue 19 (28th January 2017) - Panaitescu, Denis Mihaela; Nicolae, Cristian Andi; Frone, Adriana Nicoleta; Chiulan, Ioana; Stanescu, Paul Octavian; Draghici, Constantin; Iorga, Michaela; Mihailescu, Mona
ABSTRACT: The widespread application of poly(3‐hydroxybutyrate) (PHB) in the food packaging and biomedical fields has been hindered by its high brittleness, slow crystallization, poor thermal stability, and narrow processing window. To overcome these limitations, a mixture of biodegradable and biocompatible plasticizers was used to modify PHB. Epoxidized soybean oil (ESO), acetyl tributyl citrate, poly(ethylene glycol) 4000 (PEG4000), and poly(ethylene glycol) 6000 (PEG6000) were tested to improve PHB melt processing and to achieve balanced thermal and mechanical properties. These plasticizers increased the flexibility and decreased the melt viscosity, improving the processability. The tensile strength was maintained within the limit of experimental error for ESO and decreased slightly (6–7%) for the other plasticizers. PEG6000 and ESO delayed the decomposition process of PHB. The plasticizers did not hinder the crystallization, and poly(ethylene glycol)s increased the crystallinity. The change in the interplanar distance and crystallite size, correlated with lamellar stack dimensions, gave more information on the plasticizers' effects in PHB. The blend with 5 wt % ESO was considered suitable for the fabrication of marketable PHB films. This study showed that it is possible to tailor the rheological, thermal, and mechanical behavior of a commercial PHB through the addition of a second plasticizer. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44810. Abstract :